2020
DOI: 10.22271/chemi.2020.v8.i5v.10530
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Endophytic-Rhizospheric phosphate solubilizing bacteria of cumin and their evaluation in vitro

Abstract: The present investigation was carried out during the year 2017-18 and 2018-19 in Laboratory of Microbiology, Devision of crop production, ICAR-National Research Centre for Seed spices Ajmer, Rajasthan (India). The maximum P solubilization zone was 19 mm followed by 17 mm recorded in isolate DCU-251 which was characterized as Pseudomonas aeruginosa (Accession no. MN192165) and DCU-262 (Kosakonia oryzendophytica strain NRCSSDCU262 Accession no. MN192166), respectively. The least solubilization zone was 11 mm due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…polymyxa COW3. Our results are in agreement with studies by Di Benedetto et al (2019) and Devi et al (2020) , who had showed the PGP properties of Bacillus spp., Pseudomonas spp., and Kosakonia spp. Panneerselvam et al (2019) showed that B. subtilis strain BioCWB (570 μg ml –1 ) and B. luciferensis strain K2 (417.3 μg ml –1 ) produced higher amounts of phosphates.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…polymyxa COW3. Our results are in agreement with studies by Di Benedetto et al (2019) and Devi et al (2020) , who had showed the PGP properties of Bacillus spp., Pseudomonas spp., and Kosakonia spp. Panneerselvam et al (2019) showed that B. subtilis strain BioCWB (570 μg ml –1 ) and B. luciferensis strain K2 (417.3 μg ml –1 ) produced higher amounts of phosphates.…”
Section: Discussionsupporting
confidence: 94%
“…The collective PGP traits and nutrient solubilization properties observed in Consortia-3 were due to the bacterial mixture of K.oryzendophytica YMA7, P. kribbensis KSB, and P. polymyxa COW3. Our results are in agreement with studies by Di Benedetto et al (2019) and Devi et al (2020), who had showed the PGP properties of Bacillus spp., Pseudomonas spp., and Kosakonia spp. Panneerselvam et al (2019) showed that B. subtilis strain BioCWB (570 µg ml −1 ) and B. luciferensis strain K2 (417.3 µg ml −1 ) produced higher amounts of phosphates.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations